What is effective in promoting a healthy lifestyle in secure psychiatric settings? A review of the evidence for an integrated programme that targets modifiable health risk behaviours. Issue 3 (8th August 2016) - Long, Clive; Rowell, Arleen; Rigg, Samantha; Livesey, Frank; McAllister, Peter
Abstract : Purpose: To describe healthy lifestyle initiatives in a secure psychiatric facility and the evidence base for these interventions. Design/methodology/approach: Following a detailed review of the literature on the physical health of psychiatric inpatients, a trans-diagnostic approach to behaviour change is advocated in selected areas. Findings: Lifestyle strategy proposals were produced that incorporate the principle of 'libertarian paternalism' in making changes to eating and exercise behaviour; a programme of motivational and reinforcement strategies; and facility specific environmental restructuring to include maximising the therapeutic use of green space. Practical implications: Instituting described changes needs to be accompanied by a programme of evaluation to assess intervention specific physical health changes. Originality/value: This article provides a synthesis of findings in key areas of behaviour change relevant to improving the physical health of psychiatric patients in secure settings. It is a co-ordinated and interlinked lifestyle strategy that has applicability to similar services.